Physics students develop professional identity throughout their undergraduate programs and after graduation - Khong, Hien (Kansas State University, 2022)
College has traditionally been regarded as a critical period of time for students to develop their scientific knowledge and skills in order to be prepared for a career. This thesis investigates the impact of three overarching components throughout the undergraduate physics program on students' identity development of physics undergraduate students: physics laboratories, sense of belonging, and future career development. The first component focuses on upper-division students' interactions in the advanced physics laboratory to form equitable or inequitable collaboration. The second component investigates students' sense of belonging to their departments, which is impacted by their perceptions of departmental features. The final component involves students imagining their future professional selves and the interaction of future selves with past selves. The sum of these three overarching components provides a comprehensive picture of students' needs and issues that must be addressed in order to advocate for a meaningful physics program for all students. In this dissertation, each overarching component will be presented as a separate project. The first project investigates the dynamics of group work in mixed-gender groups of three physics students. Two theoretical constructs are used to characterize dynamics of students’ interactions: perceived expertise and inchargeness. We hypothesize that the distribution of positionings within these constructs will have an effect on equity, which is defined as everyone having a fair opportunity to access on-task discussion and experimental equipment. Observing three groups of students working on X-ray diffraction and torsional oscillation, the study found that members with high perceived expertise tend to use their confidence in discourse to direct others' behaviors and the group's activities. Group members with more perceived expertise and inchargeness have full access to on-task discussions and laboratory equipment. Conversely, the students with lower perceived expertise and inchargeness can have either full or limited access to on-task discussions and equipment. Their access depends on how the students with higher perceived expertise and inchargeness facilitate the group activities. Findings from this study suggests noticing these dynamics in the classroom and work to increase fair access to all students. The second project highlights students' perceptions of departmental features that can support or inhibit students' sense of belonging (SB). Double-majored students are selected from the data cohort to explore their sense of belonging in four departments: physics, education, math, and computer science (CS). Situating the project into the Community of Practice Framework, features of departmental communities of practice are identified that can support or diminish mutual engagement, which is defined as activities that members participate in together to build connections and relationships. Theoretically, the greater the mutual engagement between departmental members, the more likely it is that members will shift toward central membership, resulting in a strong SB in the department. The project conducted semi-structured interviews and multiple case studies to identify a set of departmental features that can impact a SB: collaboration, extracurricular activities, future career supports, and building structure. We conclude that if the four departmental features are perceived to foster the mutual engagement between students and faculty as well as among students, students are more likely to develop the central membership in the department, thereby increasing a SB. In contrast, if departmental features are perceived to be less accessible for students to form mutual engagement, students' central membership is less likely to develop, sequentially lowering students' SB. The study's implications include departmental suggestions for improving students' SB, resulting in a more inclusive learning environment for all students. The last project is situated within Possible Selves Theory to explore senior students and recent alumni in STEM envisioning future professional identity after college. Longitudinal semi-structured interviews at a large urban university in the United States were conducted to ask participants about their career plans and resources they needed to develop future possible selves. This study presents multiple case studies of four physics students exploring, adjusting, and refining their future possible selves. Overall, all case studies express well-elaborated future possible selves constructed by integrating academic and sociocultural experiences. In particular, positive academic experiences from courses, research, and conferences enhance students' interest and self-efficacy in a discipline/field, resulting in constructing future possible selves in the field. However, consistent with prior study, negative experiences such as not being valued by peers can reduce students' self-efficacy, sequentially sabotaging students’ possible selves in the field. Personality, living habits, and social identity are also incorporated in order to make future selves congruent with sociocultural experiences. Furthermore, analyzing students' narratives about futures also reveals two primary possible selves paths: a path of narrowing and refining imagined future; and a path of trying new selves in series. The findings from the three projects provide an understanding of students' dynamics in physics classrooms, as well as students' needs throughout their undergraduate programs to develop a sense of belonging and a professional identity. These insights can then be translated into implications for administrators and faculty to consider in order to create a campus environment that encourages students to progress through their undergraduate studies and into their professional lives.
Keywords: Physics education; Professional identity; Upper-division students; Equity; Future career